Pendampingan Penyusunan Laporan Keuangan Berbasis Accurate Online pada UMKM CV Putra Wijaya - Andini, Putri; Fiqhiyyah, Nuryatin; Handayani, Priska Amelia; Khotimah, Ratri Khusnul; Qomaruddin, Qomaruddin; Wahid, Al Fatur Amin; Fathurrokhim, Haedar; Rohmah, Izzana Adlia (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2024)
This service aims to increase understanding of making SAK EMKM-based financial reports using Accurate Online software, as well as introduce the use of this software and provide assistance in financial reporting to CV Putra Wijaya MSMEs in Kediri City. Service methods include observing the process of processing transactions and financial reports, training in preparing financial reports, as well as assistance in recording and preparing financial reports. The results show that the mentoring focus on resolving CV Putra Wijaya's financial reporting problems encourages the need for appropriate preparation and data collection to prepare financial reports according to applicable standards. This is expected to make a positive contribution to improving the skills and quality of MSME financial reporting.